Smart and Sustainable Civil Infrastructure for Libya’s Vision 2030 - Bsher Hassn Mohmed Askyoe (African Journal of Advanced Pure and Applied Sciences, 2025)
Civil engineering is central to achieving Libya’s Vision 2030, which emphasizes infrastructure recovery, sustainable construction, and modern urban planning. Libya’s strategic geographical location, abundant construction materials, and strong renewable energy potential provide a foundation for civil engineering-led national reconstruction. However, decades of conflict and weak institutional capacity have severely deteriorated urban infrastructure, resulting in urgent challenges for sustainable rebuilding. This paper adopts a comparative case study approach, drawing lessons from Saudi Arabia, the UAE, and Singapore, and develops a framework for implementing sustainable and smart infrastructure solutions in Libya. Using SWOT analysis, resource assessment, and cross-case evaluation, the study identifies opportunities for leveraging local resources, renewable energy integration, and digital urban planning. Results highlight critical gaps in governance, financing, and human capital, but also underline Libya’s capacity to achieve cost-effective and sustainable infrastructure development if guided by an integrated framework.